(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The present investigation was conducted to evaluate the anti-asthmatic activity of aqueous extract of the bark of Prosopis cineraria (L.) Druce to validate its traditional and ethnopharmacological use. Aqueous extract of the bark of P. cineraria (L.) Druce at doses of 100 and 200 mg/kg b.wt i.p was evaluated for the assessment of its anti-asthmatic activity using milk induced leukocytosis and eosinophilia, oxidative stress analysis in the liver and kidney, along with histopathological changes in the trachea of mice. The results of the present investigation showed that aqueous extract of bark of P. cineraria at (100 and 200 mg/kg b.wt, i.p) significantly decreased milk induced leukocytosis and eosinophilia, was effective towards restoration of enhanced levels of lipid peroxidation and reduced levels of GSH and SOD in the liver and kidney, and showed a reduction in the thickness of the tracheal wall and cartilage along with inflammatory cells in mice in a dose-dependent manner when compared with the control group. It can be concluded that aqueous extract of the bark of P. cineraria (L.) Druce possesses anti-asthmatic activity.